Reformvorschläge der Kirchensteuer in der Evangelischen Kirche in Deutschland - Thieme, Sophie (Universitätsverlag Göttingen, 2022)
It is predicted that church membership in the Protestant church in Germany will be cut in half by 2060. Church tax liability plays a central role in church resignations. Therefore, reform proposals of the church tax law are discussed to prevent church resignations, such as the exemption of young professionals from church tax liability. However, the right to tax is not a purely ecclesiastical matter but has implications for the state sector. Therefore, the collection of church taxes entails framework conditions imposed by the Constitution, which limits the church's freedom of organization. This thesis examines the reform proposals of church tax law regarding their legal feasibility and, in doing so, sheds light on the limits of the tax autonomy of religious communities. Central questions are: How flexible is the taxation right of religious communities? What is the church allowed to do? And what can it implement?